2011
DOI: 10.3858/emm.2011.43.4.027
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B is activated as an executive protease in fetal rat alveolar type II cells exposed to hyperoxia

Abstract: Alveolar type II cells are main target of hyperoxia-induced lung injury. The authors investigated whether lysosomal protease, cathepsin B (CB), is activated in fetal alveolar type II cells in the transitional period from the canalicular to saccular stages during 65%-hyperoxia and whether CB is related to fetal alveolar type II cell (FATIIC) death secondary to hyperoxia. FATIICs were isolated from embryonic day 19 rats and exposed to 65%-oxygen for 24 h and 36 h. The cells exposed to room air were used as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…It has been reported that CD147 was increased in bronchoalveolar lavage fluid obtained from COPD patients, which may suggest its modulatory role in MMP9 activation 10 . Previously published studies indicate that cathepsin B mediates human alveolar epithelial cell death stimulated by lipopolysaccharides 36 and executing fetal ATII cell death induced by ROS generated by hyperoxia 37 . Our results suggest that cathepsin B may contribute to ATII cell injury under high oxidative stress induced by CS and in emphysema as well.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CD147 was increased in bronchoalveolar lavage fluid obtained from COPD patients, which may suggest its modulatory role in MMP9 activation 10 . Previously published studies indicate that cathepsin B mediates human alveolar epithelial cell death stimulated by lipopolysaccharides 36 and executing fetal ATII cell death induced by ROS generated by hyperoxia 37 . Our results suggest that cathepsin B may contribute to ATII cell injury under high oxidative stress induced by CS and in emphysema as well.…”
Section: Discussionmentioning
confidence: 99%
“…Animal care and experimental procedures were carried out in accordance with the Guidelines for Animal Experimentation of Kangwon National University School of Medicine with the approval of the Institutional Animal Care. After extraction of fetal lungs and isolation of fetal type II cells as described previously,12,13,15,16 type II epithelial cells were harvested with 0.25% (wt/vol) trypsin in 0.4 mM EDTA and plated at a density of 10×10 5 cells/well on 6-well plates precoated with fibronectin (4 µg/well). Plates containing cells were incubated for an additional 24 h in serum-free DMEM and then incubated in a culture chamber with ProOx Oxygen Controller with Low profile right angle sensor (BioSpherix, Redfield, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For the study of preincubation of rIL-10, the cultured type II cells were treated with rIL-10 (R&D Systems, Minneapolis, MN, USA), at a concentration of 250 ng/mL,13 for 1 h before hyperoxia exposure. And for inhibition studies, the cells in an identical manner were preincubated with specific inhibitor of cathepsin B, CA074Me (Calbiochem, San Diego, CA, USA), at a concentration of 100 µM3,12 for 1 h prior to 65%-hyperoxia. The concentrations of 250 ng/mL of rIL-1013 and 100 µM cathepsin B-inhibitor3,12 were chosen based on previous studies, which showed that these concentrations greatly reduced cell death in fetal alveolar type II cells 12,13…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HALI ( 2 ), ARDS ( 3 ), chronic obstructive pulmonary diseases ( 4 ), pulmonary fibrosis ( 5 ) and other lung diseases caused by oxidative stress, are the primary reasons for type II alveolar epithelial cell (AEC-II) apoptosis. AEC-II are the primary targeting cells for high oxygen ( 2 , 6 ), AEC-II apoptosis is considered to be the underlying pathogenesis of HALI ( 7 9 ), and the inhibition of AEC-II can effectively reduce the degree of HALI apoptosis ( 10 , 11 ). The survival or apoptosis of AEC-II directly affect the degree of lung injury and repair ( 12 ).…”
Section: Introductionmentioning
confidence: 99%